2016
DOI: 10.1111/1346-8138.13558
|View full text |Cite
|
Sign up to set email alerts
|

Pazopanib does not bring remarkable improvement in patients with angiosarcoma

Abstract: Pazopanib is a potent and selective multi-targeted tyrosine kinase inhibitor that has been reported to extend progression-free survival in cases of metastatic soft-tissue sarcoma. However, the efficacy of pazopanib for cutaneous angiosarcoma has not been confirmed. We report eight cases of angiosarcoma treated with pazopanib, and review the efficacy and safety of pazopanib therapy. We retrospectively investigated the clinical information, including age, sex, body surface area, location, performance status, lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 10 publications
1
20
0
2
Order By: Relevance
“…However, Kitamura et al . have reported that pazopanib does not bring remarkable improvement in patients with CAS . Thus, the benefits of novel agents for CAS are still controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Kitamura et al . have reported that pazopanib does not bring remarkable improvement in patients with CAS . Thus, the benefits of novel agents for CAS are still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, Kitamura et al have reported that pazopanib does not bring remarkable improvement in patients with CAS. 15 Thus, the benefits of novel agents for CAS are still controversial. An early assessment of prognosis using SUV max at the initial visit may be helpful for the selection of therapies among conventional taxane chemotherapy and newly developed therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In another report, Kitamura et al . described eight individuals with CAS treated with pazopanib, suggesting that pazopanib does not achieve marked improvements in the overall survival of patients with CAS . Definitive rules for the selection of second‐line agents are thus lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported eight cases of AS treated with pazopanib, and the average PFS of these eight cases was only 1.81 months. 5 Thus, we think that the clinical efficacy of pazopanib as a treatment for AS is limited.…”
Section: Dear Editormentioning
confidence: 99%